A facile Schiff base chemical approach: towards molecular-scale engineering of N-C interface for high performance lithium-sulfur batteries. (April 2018) - Xiao, Zhichang; Kong, Debin; Song, Qi; Zhou, Shanke; Zhang, Yunbo; Badshah, Amir; Liang, Jiaxu; Zhi, Linjie
Abstract: Nitrogen-doped (N-doped) carbon has great potential in lithium-sulfur (Li-S) batteries, since N-doping can not only enhance the reaction activity of the cathode but also suppress the shuttle effect. Unfortunately, the N-C interface as a critical chemical active site is still short of a deep and detail understanding owing to the difficulty of interfacial structure engineering on the molecular scale. In this work, an interwoven coaxial cable network with ultrahigh nitrogen content of 9.56 wt% has been successfully fabricated through engineering a rationally designed Schiff-base chemistry. This in-situ bottom-up strategy enables the targeted heteroatom doping throughout the entire networks on molecular scale. Thus, a homogenous interface between nitrogen and carbon matrix can be achieved even at such a high doping level, which is demonstrated to play the key role in facilitating the chemical absorption of sulfur/polysulfides, and eventually improving the cycling stability of the electrode. Consequently, the composite demonstrates outstanding long cycling performance with a high specific capacity of 729 mAh g −1 after 500 cycles and a superior rate capability. The bottom-up strategy for fabricating the N-doped carbon networks will open up a new avenue for deeply understanding the critical role of interface in rational designing of N-doped carbon materials. Graphical abstract: An interwoven coaxial cable network with ultrahigh nitrogen content is successfully fabricated through engineering a rationally designed Schiff-base chemistry. This in-situ bottom-up strategy enables the targeted heteroatom doping throughout the entire networks on molecular scale, and the obtained homogenous N-C interface is demonstrated to play the key role in facilitating the chemical absorption of sulfur/polysulfides.fx1 Highlights: A deliberate bottom-up strategy for molecular-scale engineering of N-C interface with ultrahigh nitrogen content. The homogenous N-C interface was found to play a key role in improving the cycling stability in lithium-sulfur batteries. Excellent rate performance and cycling stability for lithium-sulfur batteries.